FEATURES OF INTRODUCTION OF REMOTE WORK IN THE ACTIVITIES OF MODERN ENTERPRISES - KHACHATRYAN, Valentyna; STRATIICHUK, Viktoriia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article presents a study on the opinions of the experience of introducing remote work in Ukraine and the world, identifies groups of negative and positive factors for the economy. The main problems of the shortcomings of the organization of remote workflow, which affected the efficiency of work, highlighted; the main economic advantages of this format of work substantiated. The article analyzes expert assessments and reveals that today Ukrainians have both interest and sufficient readiness for remote work, which confirmed by the identified characteristics and data on the level of digital literacy of the population. However, the article determines that the continuation of this practice raises many questions on the part of employers, primarily due to a whole list of organizational factors that can offset the positive effect of the introduction of a new type of labor relations. The expectations not only to intensify the use of remote work in our country, but also to expand the scope of its application identified. The considered foreign experience shows a number of quite successful examples of remote activities of companies (mainly English speaking). International research reports predict further growth in the spread of remote employment, even in those countries where this format was in limited demand before the crisis.
Keywords: enterprise; labor activity; remote work; pandemic